Entrepreneurship Education: Challenges and Efforts in North East India - Jothipaul Suresh Kumar; Devasahayam Shobana (Dera Natung Government College Research Journal)
This study gives a succinct overview of the difficulties and initiatives in North East India's entrepreneurship education. The area, which is distinguished by its distinctive sociocultural and geographical characteristics, faces particular challenges in encouraging entrepreneurial mindset and skills among its population. This study highlights the difficulties that prevent entrepreneurship education, including low awareness and mindset, infrastructure limitations, and financial barriers. Additionally, it examines the initiatives like skill development programmes, industry-academia collaboration, and support for female entrepreneurs that the government and stakeholders have undertaken to address these issues. North East India hopes to create a thriving entrepreneurial ecosystem that supports economic growth and development by acknowledging these difficulties and making focused efforts. Hence, the paper will highlight the efforts, challenges, background, present scenario, and transformation of the system of the next generation of entrepreneurship education in North East India.